The difference of surface roughness in acrylic resin self-cured with addition of zirconium dioxide particles as a denture repaired materials - Ariestania, Vivin; Teguh, Paulus Budi; Yusuf, Dedy (Indonesian Journal of Prosthodontic, 2020)
Background: Tooth loss is one of the effects of periodontal disease and dental caries. Tooth loss can be resolved by making a denture prosthesis. Several factors that influence society on denture use include aesthetic, social, func-tional, educational, and cultural factors. The large number of lost teeth will certainly increase the demand or desire to manufacture dentures to restore the function of the missing teeth. One of the materials that are often used in den-tures is acrylic resin. Acrylic resins frequently used for denture base materials are cold polymerized acrylic resin and hot polymerized acrylic resin. Cold polymerized acrylic resin uses chemical activation, and this type of resin is often used for denture repair materials. Denture repair aims to repair prostheses that have many fractures in the mid-line area. Chemical polymerization acrylic resin is often used as a repair material because it is easy to apply and can be done directly on the patient. This resin has a disadvantage because it often leaves residual monomer in the polymerization process, so it impacts porosity. This problem can be overcome by modifying the resin's chemical structure using polyethylene glycol or by adding ZrO2. Objective: This study aims to determine the effect of adding 3%, 5%, and 10% of zirconium dioxide (ZrO2) nanoparticles to the surface roughness of self-cured acrylic resin as a denture repair material. Methods: Four sample groups, each consisting of 10 samples, were divided into the con-trol group (K), the treatment group with ZrO2 addition 3% (P1), the treatment group with the addition of ZrO2 5% (P2), and the treatment group with the addition of ZrO2 10% (P3). The results of all treatments and controls were tested for surface roughness using the MST-301 surface roughness test profilometer. Results: Based on the results of the descriptive test, the mean of group K = 0.395 ± 0.161, group P1 = 0.813 ± 0.525, group P2 = 1.284 ± 0.336 and group P3 = 1.093 ± 0.558. In the Kruskal-Wallis test, there were significant differences in all groups. Conclusion: The self-cured acrylic resin with the addition of 3% concentration of ZrO2 has the lowest surface roughness com-pared to the other groups, and the roughness is almost similar to the surface roughness of the control group.